A multiscale continuum model for inelastic behavior of woven composite. (15th October 2019) - Madke, Rohit Raju; Chowdhury, Rajib
Abstract: A multiscale continuum model to predict the anisotropic non-linear behavior and strength of 2D and 3D woven composite has been proposed. The proposed approach is based on representative volume element (RVE), which serves as a two-level approximation, first at the microscale via fibers enclosed with cohesive interphase embedded in a matrix and second at the mesoscale via tows interlaced with each other and reinforced inside a matrix. The constitutive property fields of the RVE's at two scales are evaluated under periodic boundary conditions and quasi-static loading in six different directions. The mechanism's such as built-in imperfections at the surface, residual stresses and glitches that are generally neglected in such models have been incorporated combinedly in the form of cohesive interphase at lower scale. The accuracy of the proposed approach is assessed by a comparison of the literature data and the predicted results. The fundamental failure mechanism at both the scales have been addressed using preeminent failure criterions. From the various techniques used, homogenization in conjunction with finite element analysis is a precise and consistent way to analyze the nonlinear mechanical response and prediction of failure in woven composites and their tows.